Comparative Efficacy of Barbados Lilac, Pineapple And Benazol® Against Gastrointestinal Nematodes in Cattle (Progressive Agriculture, 2013)
The effect of barbados lilac (Melia azedarach, Linn., @100 mg/kg bwt. ), pineapple (Ananas comosus, Merr., @100mg/kg bwt.) and Benazol® (albendazole, @7.5 mg/kg bwt.) against natural gastrointestinal nematodes were studied in cattle. Their effect of TEC, Hb, PCV, TLC, ALT, AST and body weight were observed. Twenty four (24) naturally parasitized cattle of BAU Dairy Farm, Mymensingh were randomly divided into four groups, each consisting of six (6) cattle. Water extract of leaves of barbados lilac and pineapple were administered orally to the cattle of group A and B, respectively. Cattle of group C were treated with Benazol® orally. Cattle of group D was kept as infected control group. Fecal samples, body weight, hematological and biochemical parameters were examined before treatment and on 3rd, 10th, 17th and 28th day. A significant (p